PERTOLONGAN PERTAMA PADA CIDERA OLAH RAGA(SPRAIN STRAIN) DENGAN METODE RICE PADA PMR DI SMAN 1 PLOSOKLATEN - Didit Damayanti; Farida Hayati; Nian Afrian Nuari (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
The high level of physical activity carried out by school adolescents is one of the factors that causes the condition of the sprain strain to occur in students. The high enthusiasm for sports such as playing soccer, running and other sports can trigger the condition of a sprain strain that is difficult for students to avoid. Improving the health status of the school community can be done through various activities, one of which is the provision of first aid training for sports injuries (sprain strain) using the RICE method. Students of SMAN I Plosoklaten are a group of teenagers in a community setting who have a risk of health problems due to dynamic activities. First aid for a sprain strain can be a treatment that can be given immediately. This is to prevent the injury from getting worse. One method that can be used to treat cases of sprain strain is RICE (Rest, Ice, Compress, Elevate) by keeping the leg that has a sprain strain still, compressing it with ice or cold water to relieve pain, Giving an elastic bandage to prevent swelling and also This can be done by elevating the injured body part to improve blood flow. Community service activities in the form of Sports Injury First Aid Training (Sprain Strain) at PMR SMAN I Plosoklaten are very positive activities to be carried out in order to disseminate health knowledge so as to increase the knowledge and ability of each student in providing assistance to muscle injuries.